Detection of enteric parasites and molecular characterization of Giardia duodenalis and Blastocystis sp. in patients admitted to hospital in Ankara, Turkey. Issue 5 (28th April 2021) - Sarzhanov, Fakhriddin; Köster, Pamela Carolina; Dogruman-Al, Funda; Bailo, Begoña; Dashti, Alejandro; Demirel-Kaya, Filiz; Carmena, David
Abstract: This epidemiological study assesses the occurrence of enteric parasites in 4303 patients attended at two public hospitals in Ankara (Turkey) during 2018–2019. Microscopy was used as a screening test. Giardia duodenalis was also identified using a commercial ELISA for the detection of parasite-specific coproantigens. Giardia -positive samples by microscopy/ELISA were confirmed by real-time PCR and characterized using a multilocus genotyping scheme. Blastocystis sp. was genotyped in a sample subset. Blastocystis sp. (11.1%, 95% CI 11.4‒14.8%) and G. duodenalis (1.56%, 95% CI 1.22‒1.96) were the most prevalent pathogens found. Cryptosporidium spp., Entamoeba histolytica and intestinal helminths were only sporadically (<0.5%) found. For G. duodenalis, sequence ( n = 30) analyses revealed the presence of sub-assemblages AII (23.3%), discordant AII/AIII (23.3%) and mixed AII + AIII (6.7%) within assemblage A, and BIII (10.0%), BIV (3.3%) and discordant BIII/BIV (23.3%) within assemblage B. Two additional sequences (6.7%) were assigned to the latter assemblage but sub-assemblage information was unknown. No associations between G. duodenalis assemblages/sub-assemblages and sociodemographic and clinical variables could be demonstrated. For Blastocystis sp., sequence ( n = 6) analyses identified subtypes ST1, ST2 and ST3 at equal proportions. This is the first molecular characterization of G. duodenalis based on MLG conducted in Turkey to date.